Efektivitas Penerapan Program Beli Mahal Jual Murah (BIMAJUARA) Dalam Mensejahterahkan Petani Di Kabupaten Klungkung - Suandana, I Gede Sandi; Supriliyani, Ni Wayan; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT namely the Cheap Sale and Cheap Buy Program (BIMAJUARA). The government through the agricultural service cooperates with the KUD to buy more expensive grain from the market. In this study the researcher used the measurement of the effectiveness of Richard M Steers in Sutrisno with 3 indicators, namely goal optimization, system perspective and human behavior pressure.The data analysis technique used in this study is a descriptive qualitative analysis technique. The results of this study indicate that in the implementation of the BIMAJUARA program it has not run properly. Absorption of grain that is still very minimal is also one of the causes so that the implementation of the BIMAJUARA Program carried out by the Agriculture Service becomes less effective. Penyerapan gabah yang masih sangat minim juga menjadi salah satu penyebab sehingga penerapan Program BIMAJUARA yang dilakukan oleh Dinas Pertanian menjadi kurang oefektiv. Keywords: Effectiven service